The Good War - Williams, M. author. aut Link
XVIII, 171 p.
Keywords: The Good War tackles the issue of NATO in Afghanistan, exploring NATO's evolution in the 1990s and blending NATO's transformation from a reactive defense organization into a pro-active risk manager with the ethic of liberalism. It raises questions such as why an alliance built upon the territorial defence of Europe ended up in Afghanistan.